Progressive brain structural changes after the first year of treatment in first-episode treatment-naive patients with deficit or nondeficit schizophrenia. (30th June 2019) - Lei, Wei; Kirkpatrick, Brian; Wang, Qiang; Deng, Wei; Li, Mingli; Guo, Wanjun; Liang, Sugai; Li, Yinfei; Zhang, Chengcheng; Li, Xiaojing; Zhang, Pingping; Li, Zhe; et al.
Highlights: At baseline, DS but not NDS, had less WMV in bilateral PLIC than HCs. At follow-up, NDS showed progressive WMV reduction in bilateral PLIC, but not in DS. At both time points, GMV in cerebellar culmen was stably smaller in DS than in NDS. Abstract: Progressive brain volume atrophy has been reported in patients with schizophrenia. However, whether this progress differs between patients with primary negative symptoms (deficit schizophrenia; DS) and those without such symptoms (nondeficit schizophrenia; NDS) is unknown. Here, we examined grey matter volume (GMV) and white matter volume (WMV) changes over 12 months in 34 first-episode treatment-naive patients with schizophrenia (14 DS and 20 NDS) and 32 healthy controls (HCs) using structural magnetic resonance imaging and voxel-based morphometry. At baseline, compared to HCs, patients with DS but not NDS had less WMV in bilateral posterior limb of the internal capsule (PLIC) and cerebellar tonsil ( P  < 0.05, FDR corrected) and smaller GMV in the cerebellar culmen ( P  < 0.05, FWE corrected). At follow-up, NDS group showed WMV reduction in bilateral PLIC ( P  < 0.05, FDR corrected), while DS group showed no progressive WMV changes. While both patient groups exhibited GMV reduction in the hippocampus and insular cortex, patients with NDS showed additional GMV loss in the frontal and cingulate cortex and a selective increase in GMV in the left thalamus ( P  < 0.05 FWE corrected). Our study revealed double dissociations in developmental brain volume changes in the first year after clinical contact for psychosis in DS versus NDS patients.